Notes on the congrid eel genus Parabathymyrus from the western Pacific Ocean, with the description of a new species (Pisces: Anguilliformes: Congridae) - Ho, Hsuan-Ching; Smith, David G.; Shao, Kwang-Tsao (Zootaxa, 2015)
The congrid eel genus Parabathymyrus from the western Pacific Ocean is reviewed and three species are recognized: Parabathymyrus macrophthalmus from Japan, Taiwan, Vietnam and Australia, P. brachyrhynchus from Taiwan, Vietnam, the Philippines, Vanuatu and Solomon Islands, and a new species, P. philippinensis sp. nov., is described based on two specimens collected from the Philippines. These three species can be distinguished from each other by the number of total vertebrae (128–137 in P. macrophthalmus, 162–173 in P. brachyrhynchus and 140–141 in P. philippinensis sp. nov.), preanal vertebrae (39–46, 49–58, and 42), preanal lateral-line pores (36–44, 46–54, and 40–42), total lateral-line pores (121–131, 159–169, and 140–141) and supraorbital pores (4, 4 and 3).